2021
DOI: 10.1371/journal.pone.0256308
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of blaNDM-1 and blaVIM producing Gram-negative bacilli in ventilator-associated pneumonia at AMR Surveillance Regional Reference Laboratory in India

Abstract: Introduction Ventilator-associated pneumonia (VAP) may be a life threatening nosocomial infection encountered in intensive care units. Currently the emergence of carbapenem-resistant Gram-negative pathogens has become worrisome threat worldwide. Material and methods Endotracheal aspirates samples were collected from patients who were under mechanical ventilation for > 48 h. The bacterial isolates were identified by MALDI-TOF-MS and antibiotic susceptibility testing performed. All carbapenem resistant isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…In terms of its accuracy in detecting antimicrobial resistance genes, BFPP showed relatively high agreement when compared to VITEK-2 breakpoints, with PPA [100%, 93%, not applicable], NPA [97%, 85%, 90%], and OPA [98%, 90%, 90%] for carbapenemase producers, ESBLs, and MRSA, respectively. In comparison to other studies [28,[39][40][41] that reported on the prevalence of carbapenemase producers and ESBLs among HAP patients, our results revealed a higher rate of detection. This higher resistance rate could be attributed to the large use of antimicrobial agents among ICU patients, leading to more selective pressure and the appearance of different resistant phenotypes.…”
Section: Discussioncontrasting
confidence: 91%
“…In terms of its accuracy in detecting antimicrobial resistance genes, BFPP showed relatively high agreement when compared to VITEK-2 breakpoints, with PPA [100%, 93%, not applicable], NPA [97%, 85%, 90%], and OPA [98%, 90%, 90%] for carbapenemase producers, ESBLs, and MRSA, respectively. In comparison to other studies [28,[39][40][41] that reported on the prevalence of carbapenemase producers and ESBLs among HAP patients, our results revealed a higher rate of detection. This higher resistance rate could be attributed to the large use of antimicrobial agents among ICU patients, leading to more selective pressure and the appearance of different resistant phenotypes.…”
Section: Discussioncontrasting
confidence: 91%
“…In this study, bla NDM was the most prevalent gene among K. pneumoniae isolates. Concurring with our finding, a study in India found bla NDM in 28.8% and bla VIM in 17.7% of K. pneumoniae isolates among VAP patients [ 32 ]. However, a study from Iran revealed that bla VIM was the most prevalent gene (13.6%), while both bla IMP and bla NDM were only detected in two K. pneumoniae isolates [ 33 ], which is not in concordance with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Of their 172 isolates, 21.5% exhibited the presence of bla NDM genes, 17.4% exhibited the presence of bla VIM gene and 8.7% isolates harbored both bla NDM and bla VIM genes. None of the isolates contained bla IMP gene [ 32 ]. Sękowska et al confirmed that bla NDM and bla VIM genes are the main antibiotic-resistance genes that induce resistance patterns to carbapenems among VAP patients in Poland [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Meanwhile, Chen et al, Kumari et al, and Sadigov et al reported that A. baumannii was the most prevalent CR-GNB pathogen, accounting for 78.7%, 37.4%, and 37.1%, respectively. [38][39][40] This variation could be the result of geographical differences between the countries, patient population and clinical setting. 20 Determination of whether the gram-negative isolate is a carbapenemase producer is essential for epidemiological studies and also for selection of the appropriate treatment for infections.…”
mentioning
confidence: 99%